Adjuvant application of trastuzumab in HER2 positive breast cancer and impact on time to relapse - Dukic, Nikolina; Gojkovic, Zdenka; Vladicic-Masic, Jelena; Masic, Srdjan; Lalovic, Nenad; Popovic, Sladjana (Archive of Oncology, 2019)
Background: Of all breast cancers 20-25% are HER2 positive. Overexpression of HER2 protein on the surface of the malignant cell leads to excessive cell proliferation through different signaling pathways. Trastuzumab is a human monoclonal antibody that binds to domain IV of HER2 receptor and blocks signaling pathway for proliferation. The result is an improved prognosis for HER 2 positive breast cancer patients, even when compared to patients with other types of breast cancers. Methods: The study presents 74 women patients with early HER2 positive breast cancer who were previously operated (either radicaly or using breast conserving surgery), and received adjuvant chemo- and radiotherapy.  Fourty four patients received adjuvant trastuzumab for one year, and 30 patients did not (control group). Observed time to relapse of the disease was 60 months. Results: There was a significant difference in survival in favor of the group that received trastuzumab (p
Keywords: Cancer; HER2; Tyrosine kinase receptor; Trastuzumab; Prognosis; Breast; Antibodies